Supercritical carbon dioxide extraction of acorn oil - Bernardo-Gil, M. Gabriela; Lopes, Isabel M. G.; Casquilho, Miguel; Ribeiro, M. Albertina; Esquível, M. Mercedes; Empis, José (The Journal of Supercritical Fluids, 2007)
Acorn fruit oil of Quercus rotundifolia L. (holm-oak) was extracted with compressed carbon dioxide in the temperature range of 35–60 ◦ C and in the pressure range of 12–21 MPa. The inﬂuences of particle size, CO2 density, solvent ﬂow rate, and extractor geometry were studied. Two different tubular extractors were used: extractor 1 of 0.2 L of capacity, internal diameter D = 45.7 mm, height/diameter ratio H/D = 1.5, and extractor 2 of 0.09 L of capacity, internal diameter D = 21.3 mm, and H /D = 12. It was found that the yield and the initial extraction rate depend on the carbon dioxide density and superﬁcial velocity, and on the ratio of bed height to D, at the same conditions of temperature, pressure, and particle size. In the beginning of extraction, CO2 density is the preponderant factor, but after some time of extraction, the fraction of oil directly exposed to the solvent, which is dependent on particle size, becomes the most important factor. The Sovova model was successfully applied to the description of the supercritical extraction curves of acorn oil
Keywords: acorn; Extraction; Quercus rotundifolia L.; Sovová model; Supercritical carbon dioxide

Supercritical carbon dioxide extraction of acorn oil - Bernardo-Gil, M Gabriela; Lopes, Isabel M G; Casquilho, Miguel; Ribeiro, M Albertina; Esquível, M Mercedes; Empis, José (The Journal of Supercritical Fluids, 2007)
Acorn fruit oil of Quercus rotundifolia L. (holm-oak) was extracted with compressed carbon dioxide in the temperature range of 35–60 ◦ C and in the pressure range of 12–21 MPa. The inﬂuences of particle size, CO2 density, solvent ﬂow rate, and extractor geometry were studied. Two different tubular extractors were used: extractor 1 of 0.2 L of capacity, internal diameter D = 45.7 mm, height/diameter ratio H/D = 1.5, and extractor 2 of 0.09 L of capacity, internal diameter D = 21.3 mm, and H /D = 12. It was found that the yield and the initial extraction rate depend on the carbon dioxide density and superﬁcial velocity, and on the ratio of bed height to D, at the same conditions of temperature, pressure, and particle size. In the beginning of extraction, CO2 density is the preponderant factor, but after some time of extraction, the fraction of oil directly exposed to the solvent, which is dependent on particle size, becomes the most important factor. The Sovova model was successfully applied to the description of the supercritical extraction curves of acorn oil
Keywords: acorn; Extraction; Quercus rotundifolia L.; Sovová model; Supercritical carbon dioxide